Everydayness of Peace and War - Bukrieieva, Irina (Global Journal of Cultural Studies, 2024)
The article examines everydayness as an integrative sphere of society, which is dominant for a person since it is at the micro level that an individual forms his or her social reality. Dialectical relationships between the individual and the general can be traced in everydayness, a semantic content is formed, which makes it possible to understand what happens every day in the everyday life of a person. Therefore, everyday life acts as one of the mechanisms of formation of values, socialization and a source of formation of social capital at the micro-, meso-, and macro levels. On the basis of empirical data, it is shown that social capital accumulates in the everyday sphere, which is strong and can withstand external aggressive manifestations, such as Russia’s war against Ukraine. Ukrainian society can withstand full-scale military aggression due to solidarity ties, dense network communications, and social trust at the level of horizontal relationships. In this way, everyday life has a latent effect on the functioning of social institutions at the level of the city and the state which are the field of implementation of people's everyday routines.